The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/mcp.m500348-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine Cysts of the Breast

Abstract: Up to one-third of women aged 30 -50 years have cysts in their breasts and are presumed to be at increased risk of developing breast cancer. Here we present an extensive proteomic and immunohistochemistry (IHC) study of breast apocrine cystic lesions aimed at generating specific biomarkers and elucidating the relationship, if existent, of apocrine cysts with cancer phenotype. To this end we compared the expression profiles of apocrine macrocysts obtained from mastectomies from high risk cancer patients with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 97 publications
(95 reference statements)
3
14
0
Order By: Relevance
“…To determine if FABP7 and HMGCS2 antibodies are specific enough in terms of IHC staining to identify benign and malignant apocrine lesions [2], [16] we used a three-pronged strategy developed in our laboratory and described in detail elsewhere [23]: (i) analysis of potential cross-reactivity by 2D Western blotting (2D-WB), (ii) mass spectrometry validation of corresponding silver-stained protein spots superimposed with 2D-WB and (iii) IHC experiments with blocking of antibodies with a corresponding protein/epitope. This approach combines the intrinsic sensitivity and cellular resolution of IHC, with the specificity of 2D-WB and MS-based identification, and the overall protein analysis capability of gel-based proteomics [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine if FABP7 and HMGCS2 antibodies are specific enough in terms of IHC staining to identify benign and malignant apocrine lesions [2], [16] we used a three-pronged strategy developed in our laboratory and described in detail elsewhere [23]: (i) analysis of potential cross-reactivity by 2D Western blotting (2D-WB), (ii) mass spectrometry validation of corresponding silver-stained protein spots superimposed with 2D-WB and (iii) IHC experiments with blocking of antibodies with a corresponding protein/epitope. This approach combines the intrinsic sensitivity and cellular resolution of IHC, with the specificity of 2D-WB and MS-based identification, and the overall protein analysis capability of gel-based proteomics [24].…”
Section: Resultsmentioning
confidence: 99%
“…With the aim to develop molecular criteria to reproducibly categorize IACs at the protein level we have undertaken a systematic proteomic analysis of well-defined set of apocrine carcinomas aimed at identifying biomarkers that may characterize and subtype these lesions to a greater detail, and to search for targets that may lead to the development of novel targeted therapies and chemoprevention strategies [2], [16], [17], [18], [19]. Accordingly, we have identified a number of apocrine protein markers that include 15-prostaglandin dehydrogenase (15-PGDH) and acyl-CoA synthetase medium-chain family member 1 (ACSM1) which together with a set of categorizing markers that are predominantly expressed (AR, CD24) or not expressed (bcl-2, GATA-3) by apocrine metaplastic lesions in benign breast lesions, were proven to be specific for both apocrine ductal carcinoma in situ (ADCIS) and IAC [2], [16], [17], [19], [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach is along the line of the work of Celis et al [35,36], who analyzed the proteins found in the interstitial fluid that perfuses either the breast tumor microenvironment or the adipose tissue, and the work of Tammen et al [21], who analyzed the peptides and low molecular weight proteins extracted from tissues. Both methods identified also potentially "accessible" proteins (without chemical modifications) and were highly promising sources of biomarkers.…”
Section: Discussionmentioning
confidence: 98%
“…It has been successfully used for protein analysis over more than three decades, and it is increasingly used in disease exploration [1][2][3][4]. Using 2-DE to map thousands of proteins presents the researcher with valuable information about a specific biological system.…”
Section: Introductionmentioning
confidence: 99%